Human Rights Implications of Child Trafficking in Conflicts Situations: Case Study of The Conflict in The EnglishSpeaking Regions of Cameroon - Ndinge Nadia Mbella (Zien Journals, 2021)
The escalation of global conflicts has increased the displacements of people; leaving many impoverished and vulnerable to societal ills like trafficking in persons (TIP). TIP is a gross violation of the fundamental human rights of individuals undermining their dignity. Amongst victims, children are especially vulnerable because they can be easily manipulated and are completely dependent on adults for livelihood and support. Although Cameroon has made significant strides towards curbing the ill through the passing of Law No 2011/024 Relating to the Fight against Trafficking in Persons and Slavery, the phenomenon is more prevalent in the country with the ongoing conflicts in the English-Speaking Regions that begun in 2016. This paper addresses the human rights implications of child trafficking on victims and adopts the qualitative research methodology which uses the doctrinal method of content analysis of existing literature.
Keywords: Conflicts; Trafficking in Persons; Child Trafficking; Human Rights